2019
DOI: 10.1177/0961203319846387
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the self-directed format of Walk With Ease in patients with systemic lupus erythematosus: the Walk-SLE Pilot Study

Abstract: Objective To conduct a proof-of-concept pilot evaluation of the self-directed format of Walk With Ease (WWE), a 6-week walking program developed for adults with arthritis, in patients with systemic lupus erythematosus (SLE). Methods This was a single arm, 6-week pre- and post-evaluation of the self-directed WWE program to assess feasibility, tolerability, safety, acceptability, and effectiveness. Adult patients with physician-diagnosed SLE were recruited to participate during regularly scheduled visits to an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Previous studies [20,21] indicate that exercise can lead to various benefits in patients with systemic lupus erythematosus due to an increased aerobic capacity, exercise tolerance, and quality of life as well as decreased depressive symptoms and symptoms of fatigue. These positive effects were achieved in supervised as well as unsupervised exercise programs [15,[17][18][19]22,37,38]. In addition, it has been repeatedly discussed whether physical activity leads to an increase in lupus disease activity-an increase in autoantibodies, an increase in the consumption of complement factors, and an exacerbation of clinical symptoms such as arthralgia and myalgia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [20,21] indicate that exercise can lead to various benefits in patients with systemic lupus erythematosus due to an increased aerobic capacity, exercise tolerance, and quality of life as well as decreased depressive symptoms and symptoms of fatigue. These positive effects were achieved in supervised as well as unsupervised exercise programs [15,[17][18][19]22,37,38]. In addition, it has been repeatedly discussed whether physical activity leads to an increase in lupus disease activity-an increase in autoantibodies, an increase in the consumption of complement factors, and an exacerbation of clinical symptoms such as arthralgia and myalgia.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with systemic lupus erythematosus frequently suffer from fatigue in their daily life, so the burden of being physically active is much higher than it is for healthy patients. But when the patients are physically active, a reduction in fatigue could already be observed after a walking program of 6 weeks [22]. Thus, an individually adapted training program (based on training status and time of training) could be continuously and easily used by patients and to positively support permanent use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Musculoskeletal pain affects 50-61% of lupus patients, with morning stiffness affecting about half and fatigue affecting up to 60-90% of people with lupus (Sheikh et al 2019).…”
Section: Lupus and Quality Of Lifementioning
confidence: 99%
“…This study also showed that other than musculoskeletal manifestations and cardiopulmonary involvement, fatigue, fibromyalgia, and depression had been presented as barriers to physical activity for people with lupus (2021) Previous research involving prescribing aerobic physical activity to individuals with lupus showed statistically significant improvements in body pain reduction, fatigue, and quality of life. So, in a study conducted by Sheikh et al (2019), the researchers wanted to evaluate the effectiveness of a six-week walking program for individuals with lupus. The researchers for this study used self-reported questionnaires to receive the participants' feedback on the walking program and how it has impacted their quality of life.…”
Section: Previous Studiesmentioning
confidence: 99%